A phase II study of palliative radiotherapy combined with zoledronic acid hydrate for metastatic bone tumour from renal cell carcinoma. (1st September 2020) - Harada, Hideyuki; Shikama, Naoto; Wada, Hitoshi; Uchida, Nobue; Nozaki, Miwako; Hayakawa, Kazushige; Yamada, Kazunari; Nagakura, Hisayasu; Ogawa, Hirofumi; Miyazawa, Kazunari; Katagiri, Hirohisa; Nakamura, Naoki
Abstract: Purpose: Palliative radiotherapy is the standard of care for bone metastases. However, skeletal-related events, defined as a pathologic fracture, paraplegia, surgery or radiotherapy for local recurrence, or severe pain in previously irradiated bone with radio-resistant histology type still present high incidence. The primary objective of this study was to determine whether zoledronic acid hydrate and palliative radiotherapy could prevent local skeletal-related events. Methods: Eligible patients with bone metastases from renal cell carcinoma were treated with zoledronic acid hydrate every 3 or 4 weeks and concurrent palliative radiotherapy of 30 Gy in 3 Gy fractions. The criteria for radiotherapy were established by the treating physician, but patients with complicated bone metastases (impending pathological fracture or spinal cord compression) which needed immediate surgery were excluded. The primary endpoint was the local skeletal-related event-free survival rate at 1 year. Results: Twenty-seven patients were included in the study. The median age was 65 (range, 50–84) years. Radiotherapy dose was 30 Gy for all patients except 1 whose radiotherapy was terminated due to brain metastasis progression at 18 Gy. Zoledronic acid hydrate was administered in a median of 12 (range, 0–34) times. The median follow-up period was 12 months and 19 months in patients who were still alive. Of 27 patients in the efficacy analysis, the 1-year local skeletal-related event-free rate was 77.6% (80% confidence interval, 66.2–89.0). Common grade 3 toxicities were hypocalcemia (1 [4%]), sGPT level increase (1 [4%]) and sGOT level increase (1 [4%]). There was no grade 4 or 5 toxicity. Conclusion: Zoledronic acid hydrate administration and palliative radiotherapy were a well-tolerated and promising treatment reducing skeletal-related events for bone metastases from renal cell carcinoma. Abstract : We treated 27 patients with bone metastasis from renal cell carcinoma by radiotherapy and zoledronic acid. This study met the primary endpoint; the 1-year local skeletal-related event free rate was 77.6%.